Relationship between viability of thawed semen and pregnancy rate of Nelore cows subjected to fixed-time artificial insemination (Research, Society and Development, 2021)
This research aimed to evaluate the relationship of membrane integrity analysis, mitochondrial cytochemical analysis, and sperm kinetics of bovine semen after thawing and the pregnancy rate in Nelore females submitted to fixed-time artificial insemination (FTAI). Thirty-seven conventional semen straws, from 16 Nelore bulls and 3 Aberdeen Angus bulls were used. The semen samples were evaluated in conventional microscopy for sperm motility, vigor, and morphology, through flow cytometry for membrane integrity and mitochondrial function, and the CASA system for evaluation of sperm kinetics. All females were subjected to the same FTAI protocol and were inseminated by the same technical team. The correlation between all variables was performed by Pearson's correlation. Cluster analysis was used to analyze the relationship between pregnancy rate and combinations of laboratory tests (P ≤ 0.05). Semen samples from Angus bulls (89.2 ± 5.5) presented superior VSL (P=0.004) to Nelore semen (78.6 ± 8.6), but this did not affect the pregnancy rate (Nelore: 51.0% versus Angus: 50.5%, P > 0.05). By flow cytometry, 44.3% membrane integrity and 47.3% mitochondrial integrity were identified. Five clusters were selected, one of which presented the best pregnancy rate, containing the most balanced rates between progressive velocity and mitochondrial activity (VSL 71.16 μm/s, MITO 49.69%, TxP 62.4%). Samples of thawed bovine semen with progressive velocity and balanced mitochondrial activity demonstrated better fertility to TAI program.